Technological Solutions to Social and Citizen Problems. The Case of Civic and Public Challenges in Mexico - Martin Adalberto TENA-ES (Ediciones Universidad de Salamanca, 2017)
This paper describes the process of civic innovation that, based on technological solutions and open initiatives, the civic society's organization Codeando México suggests for the attention and solution of social and civic problems in Mexico. The Retos Cívicos (Civic Challenges) and Retos Públicos (Public Challenges) initiatives are addressed and described as experiences of innovation in the implementation of technological strategies for the solution of social and civic problems. A reflection is made on the civic appropriation of the ICTs and its irruption in the processes of innovation, as well as on the impact that the ICTs have in the conformation of a new civic ecosystem. Last, the strategies of Hacking cívico (Civic Hacking) and Comunidades Cívicas (Civic Communities) that the Codeando México organization promotes as a model for the linkage and civic participation within the frame of civic innovation, are mentioned.